University women in Spain: From the beginning to the current time - Guil Bozal, Ana; Flecha García, Consuelo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article provides an analysis of the quantitative evolution of the women presence in Spanish universities, from the nineteenth-century pioneers to the beginning of the new millennium. Based on the assumption that the social context and the widespread mentality about the women’s status did not look with favor to this kind of decisions, the objective is to publicize the clear and progressive increase in university classrooms, students first and then professors. The methodology used has begun with a review of the available literature on this subject, it is not very abundant but the data and the information provided is accurate; Below has been sought in the primary sources that keep the university files and the State administration, in the historical series of the Statistical Yearbooks fromnational and international reach. The synthesis, contrast, and systematization of all the located data has allowed us to cover the predicted purpose and to offer  a diachronic picture of the women who chose the university project as training first and then professional. The reading of these pages allows checking some of the characteristics of a long-term temporary cadence, almost one hundred and fifty years, and the reached situation of the beginning of the twenty-first century where we did not achieve yet genuine and real equal opportunities in the academic environments.